2010
DOI: 10.1016/j.jasms.2010.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the internal energy deposition of direct analysis in real time and electrospray ionization time-of-flight mass spectrometry

Abstract: The internal energy (E int ) distributions of a series of p-substituted benzylpyridinium ions generated by both direct analysis in real time (DART) and electrospray ionization (ESI) were compared using the "survival yield" method. DART mean E int values at gas flow rates of 2, 4, and 6 L min Ϫ1 , and at set temperatures of 175, 250, and 325°C were in the 1.92-2.21 eV range. ESI mean E int at identical temperatures in aqueous and 50% methanol solutions ranged between 1.71 and 1.96 eV, and 1.53 and 1.63 eV, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…As a whole, the number of stable water cluster isomers increases exponentially with n [24]. The higher abundance of specific clusters has been observed previously with DART [20], but that study showed relative higher levels of water clusters n=3, 6, 9, and 12 for various temperatures (175, 250, and 325°C) and flow rates (2, 4, and 6 Lmin ). Although there are no significant differences in binding energies [25] and bond dissociation energies [26] for water clusters in the range 9≤n≤17, the atmospheric pressure interface in the instrument used in this study (GIST-capillarydual ion funnel) is much different than that in previous work (cone/skimmer orifice) [20].…”
Section: Ion Suppressionsupporting
confidence: 53%
See 3 more Smart Citations
“…As a whole, the number of stable water cluster isomers increases exponentially with n [24]. The higher abundance of specific clusters has been observed previously with DART [20], but that study showed relative higher levels of water clusters n=3, 6, 9, and 12 for various temperatures (175, 250, and 325°C) and flow rates (2, 4, and 6 Lmin ). Although there are no significant differences in binding energies [25] and bond dissociation energies [26] for water clusters in the range 9≤n≤17, the atmospheric pressure interface in the instrument used in this study (GIST-capillarydual ion funnel) is much different than that in previous work (cone/skimmer orifice) [20].…”
Section: Ion Suppressionsupporting
confidence: 53%
“…The higher abundance of specific clusters has been observed previously with DART [20], but that study showed relative higher levels of water clusters n=3, 6, 9, and 12 for various temperatures (175, 250, and 325°C) and flow rates (2, 4, and 6 Lmin ). Although there are no significant differences in binding energies [25] and bond dissociation energies [26] for water clusters in the range 9≤n≤17, the atmospheric pressure interface in the instrument used in this study (GIST-capillarydual ion funnel) is much different than that in previous work (cone/skimmer orifice) [20]. Therefore, we believe that the observed differences in water cluster species are an effect caused more by the ion transfer optics design and reduced pressure region architecture than the by preferential formation or reactivity of particular species.…”
Section: Ion Suppressionsupporting
confidence: 50%
See 2 more Smart Citations
“…For example, TAGs have been detected from olive oil desorbed from a glass rod, with a ten-fold increase in signal observed by doping ammonia into the gas stream to facilitate [M+NH 4 ] + ion formation [241]. However, desorption/ionization of TAGs resulted in significant fragmentation, a phenomenon not uncommon in DART and one that generally increases with gas temperature [245,246]. This leads to formation of DAG-like ions with greater abundance than ions arising from intact TAG molecules, thereby reducing sensitivity and making…”
Section: Direct Analysis In Real Time (Dart)mentioning
confidence: 99%